2004
DOI: 10.1002/polb.20117
|View full text |Cite
|
Sign up to set email alerts
|

Molecular deformation mechanisms of isotactic polypropylene in α‐ and β‐crystal forms by FTIR spectroscopy

Abstract: The orientation behavior of isotactic polypropylene (iPP) in ␣and ␤-crystal form was investigated by rheo-optical Fourier transformed infrared (FTIR) spectroscopy. This method enabled quantification of the degree of orientation as a feature of structural changes during uniaxial elongation in not only the crystalline phase but also the amorphous one. Molecular orientation mechanisms can be successfully derived from experimental results. Generally, three mechanisms were detected for iPP: (1) interlamellar separa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
45
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(54 citation statements)
references
References 38 publications
5
45
0
Order By: Relevance
“…The effect of filler type and amount on the PP polymorphism and lamella thickness was studied by XRD and MDSC. Isotactic PP can exhibit four crystal structures: monoclinic (α), trigonal (β), triclinic (γ), and smectic (δ), whose formation depends on the melting history, crystallization temperature, pressure, and cooling rate, and the presence of nucleating agents or fillers . In particular, α‐form is the most common crystalline phase, while β‐−form more likely occurs under particular conditions in terms of temperature gradients, presence of shearing forces , or nucleating agents, whereas the γ‐form is the least common and is more likely to be observed in low molecular weight PP .…”
Section: Resultsmentioning
confidence: 99%
“…The effect of filler type and amount on the PP polymorphism and lamella thickness was studied by XRD and MDSC. Isotactic PP can exhibit four crystal structures: monoclinic (α), trigonal (β), triclinic (γ), and smectic (δ), whose formation depends on the melting history, crystallization temperature, pressure, and cooling rate, and the presence of nucleating agents or fillers . In particular, α‐form is the most common crystalline phase, while β‐−form more likely occurs under particular conditions in terms of temperature gradients, presence of shearing forces , or nucleating agents, whereas the γ‐form is the least common and is more likely to be observed in low molecular weight PP .…”
Section: Resultsmentioning
confidence: 99%
“…Figure 6 depicts the examples of IR spectra obtained from skin, intermediate and core layer of virgin bars and the same position in the virgin and annealed samples, respectively. In the desired wavenumber range, the 998 cm −1 band corresponds to the crystalline phase, whereas the 973 cm −1 band is contributed by both the amorphous and crystalline phases [34, 35]. The absorbance difference between parallel and perpendicular spectra is related to molecular orientation that can be quantitatively calculated through Eqs.1 and 2 .…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that the crystalline modification, spherulite size, and number of intra‐ and inter‐spherulitic tie molecules are directly related to fracture toughness of neat PP [1]. In an excellent article on the deformation behavior of iPP, Huy et al [9] have used Fourier transform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM), transmission electron microscopy (TEM), and atomic force microscopy (AFM) techniques to elucidate structural differences between α‐ and β‐PP on the micro‐ and nano‐scale and to relate them to the differences in deformation response. Under standard polymerization and processing conditions, monoclinic α‐modification dominates the iPP morphology, consisting of two populations of lenticular lamellae arranged with their axes roughly perpendicularly [10].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the hexagonal β‐modification exhibits broad lamellae structure with the lamellae forming coplanar stacks. It has been shown, that improvement of fracture resistance at high strain rates can be obtained by enhancing extent of β‐crystalline phase in common PP using β‐nucleating agents [9, 11–20]. It has been demonstrated that, during fracture, the β‐spherulites allow for better dissipation of the strain energy compared with the α‐PP [9, 18].…”
Section: Introductionmentioning
confidence: 99%